High Temperature Mechanical Properties and Fracture Mechanism of 9Cr-2W-3Co Martensitic Heat-resistant Steel - Geng Wei, Zhu Zhibao, Ma Jinhui, Song Xinli (Teshugang)
The microstructure of normalized & tempered 9Cr-2W-3Co martensitic heat-resistant steel and its tensile strength and fracture mechanism at different strain rates （5×100， 5×10-1， 5×10-2， 5×10-3， 5×10-4 s-1） at 625 ℃ was researched. The results showed that the tempered lath martensitic structure of 9Cr-2W-3Co martensitic heat-resistant steel was mainly structure obtained after normalizing and tempering， and there were a large number of chromium-containing carbide precipitation phase at the interface between the original austenite grain boundary and the lath bundle， and a certain density of dislocations in the matrix. The test steel was stretched at 625 ℃， with the increasing of strain rate， the yield strength of steel increased from 237 MPa to 430 MPa， the tensile strength was increased from 268 MPa to 480 MPa， and the reduction of area was between 28% and 15.5%. The test steel was stretched at 625 ℃， with the strain rate， the yield strength increased from 237 MPa to 430 MPa， the tensile strength increased from 268 MPa to 480 MPa， and the sectional shrinkage was 28% to 15.5%. There were a large number of dimples of different sizes in the fracture， and there were high density dislocation in the test steel matrix at different strain rates. The dislocation interacts with the interface of inclusions or lath or precipitates， leading to the initiation and expansion of micropores， and eventually the fracture of the material.